Accelerating Clean, Green, and Climate-Resilient Growth in Vietnam : A Country Environmental Analysis - World Bank (Washington, DC : World Bank, 2022)
Vietnam has demonstrated great and almost unrivaled development success over the past few decades as evidenced by a variety of measures, including national income, poverty reduction, and access to services. However, Vietnam’s performance in terms of progress on robust, equitable and sustainable development, an overarching objective of the country’s current policy framework, highlights that Vietnam is comparing less favorably when benchmarked against countries at similar income level, in the East Asia and Pacific region or globally, especially on the environment and resource efficiency. The shortcomings in critical areas of development point to important areas for policy action and investments in relation to the environment, especially as Vietnam strives to ascend to upper-middle-income country status (a level at which countries’ international and regional peers generally perform significantly higher). These include measures to rapidly decouple economic activities from polluting fossil fuel consumption (and advance renewable energy); make agriculture and industry more resource-efficient, cleaner, and productive; boost social resilience to natural disasters; and climate-proof infrastructure. Considering today’s rampant pollution and highly concerning degradation of the natural environment, it is critical that Vietnam accelerates its shift to a growth model that is cleaner, greener, and more climate resilient. The current 2021–30 Socio-Economic Development Plan (SEDP) and subordinate strategies (such as the new Green Growth Strategy) are already motivated by the overarching policy orientation toward sustainability. And the recent commitment to achieve a carbon-neutral economy by midcentury gives additional impetus to this critical transition. Moving toward a more circular economy, in essence a more resource efficient industry and harnessing the potential of renewable resources to reduce leakage and pollution, in key sectors and value chains can unlock significant growth potential and help reverse the current trends. Many of the necessary interventions, based on first-order estimates, can yield significant benefits relative to costs. Conversely, continuing the growth model of the past decades would result in cumulative costs that create a drag on the economy. Market-based instruments (including taxing carbon emissions and polluting materials such as plastics), if designed well, can unleash economic forces and leverage private sector investments that can simultaneously boost Vietnam’s sustainability, economic growth, and competitiveness.